IKABOGA Women Leadership Dan Komitmen Organisasi Sebagai Pemoderasi Determinan Akuntabilitas Pengelolaan Keuangan - Pituringsih, Endar; Sokarina, Ayudia; Asmony, Thatok (E-Jurnal Akuntansi, 2023)
The purpose of this study was to analyze and provide empirical evidence regarding the effect of presentation of financial statements and the effect of accessibility of financial reports on financial management accountability with women's leadership and organizational commitment as moderating variables. The population of this research is the management of IKABOGA organizations throughout the island of Lombok with a total of 60 respondents. Collecting data using a survey method in the form of a questionnaire. By using the census method, all populations become respondents. The data analysis method used in this study is the MRA (Moderate Regression Analysis) method with the help of the SPSS 23 program. The results show that the presentation of financial statements has a positive and significant effect on financial management accountability. The accessibility of financial reports has a positive and insignificant effect on financial management accountability. Women's leadership does not strengthen the influence of financial report presentation on financial report accountability. Women's leadership does not strengthen the influence of financial report accessibility on financial report accountability. Organizational commitment does not strengthen the influence of financial report presentation on financial management accountability. Organizational commitment does not strengthen the influence of financial report accessibility on financial management accountability. Keywords: Presentation of Financial Statements; Accessibility of Financial Reports; IKABOGA Women Leadership; Organizational Commitment; Financial Management Accountability.